Genomic Analysis of 96 Paenibacillus larvae Bacteriophages Including 26 from Aotearoa, New Zealand - Danielle N. Kok; Sophia P. Gosselin; Brenham Howard; Steven G. Cresawn; Philippos K. Tsourkas; Heather L. Hendrickson (Viruses)
The bacterium Paenibacillus larvae is responsible for the devastating honey bee (Apis mellifera) disease American Foulbrood. Research into bacteriophages that infect P. larvae is growing rapidly due to increasing antibiotic resistance and restrictions on antibiotic use in beehives in some countries. In this study, we present the sequenced and annotated genomes of 26 novel P. larvae phages recently isolated in New Zealand, which brings the total number of sequenced and annotated P. larvae phages to 96. The 26 novel phages belong to the pre-existing Vegas or Harrison clusters. We performed a comprehensive genomic analysis of all 96 phage genomes, grouping them into five divergent clusters and two singletons. The majority of these phages are temperate, with the possible exception of three phages that may be lytic. All 96 of these phages encode an N-acteylmuramoyl-L-alanine amidase that serves as their lysin. The amidases are from two divergent clusters, both of which show a high degree of intra-cluster similarity. Six phages and a prophage contain the Plx1 P. larvae toxin gene, which we suggest may be mobilizable. This study expands our knowledge of P. larvae phages from around the world.